Häufige Varianten des EPDR1-Gens und das Risiko für das Auftreten eines Morbus Dupuytren - Dębniak, T.; Żyluk, A.; Puchalski, P.; Serrano-Fernandez, P. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2013)
The object of this study was the investigation of 3 common variants of single nucleotide polymorphisms of the ependymin-related gene 1 and its association with the occurrence of Dupuytren’s disease. DNA samples were obtained from the peripheral blood of 508 consecutive patients. The control group comprised 515 healthy adults who were age-matched with the Dupuytren’s patients. 3 common variants were analysed using TaqMan® genotyping assays and sequencing. The differences in the frequencies of variants of single nucleotide polymorphisms in patients and the control group were statistically tested. Additionally, haplotype frequency and linkage disequilibrium were analysed for these variants. A statistically significant association was noted between rs16879765_CT, rs16879765_TT and rs13240429_AA variants and Dupuytren’s disease. 2 haplotypes: rs2722280_C+rs13240429_A+rs16879765_C and rs2722280_C+rs13240429_G+rs16879765_T were found to be statistically significantly associated with Dupuytren’s disease. Moreover, we found that rs13240429 and rs16879765 variants were in strong linkage disequilibrium, while rs2722280 was only in moderate linkage disequilibrium. No significant differences were found in the frequencies of the variants of the gene between the groups with a positive and negative familial history of Dupuytren’s disease. In conclusion, results of this study suggest that EPDR1 gene can be added to a growing list of genes associated with Dupuytren’s disease development.
Keywords: M. Dupuytren; genetic disposition; ependymin-related gene 1